PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM - NICO ALEXANDER; NICKEN DESTRIANA (Jurnal Bisnis dan Akuntansi, 2013)
The objective of this research is to investigate the influence of economic value added, operating cash flow, residual income, earnings, operating leverage, market value added and dividend yield to stock return. The data selected by using purposive sampling method and there are 26 manufacturing companies that public listing in Indonesia Stock Exchange from 2008 until 2011 as research sample. This research uses multiple regression as the data analysis. The empirical results of this research show that economic value added, operating cash flow, residual income, earnings, market value added have influence to stock return while operating leverage and dividend yield haven’t influence to stock return.